Psikoedukasi Mengatasi Toxic Parenting Bagi Remaja - Novita Maulidya Jalal; Rahmawati Syam; St.Hadjar Nurul Istiqamah; Wilda Ansar; Ismalandari Ismail (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
The presence of a child is the biggest and most beautiful gift for every parent. Parents in a family have an obligation to provide all needs including basic needs to their children. Parents raise their children with certain patterns, including parents who raise authoritarian, democratic or permissive patterns. children, manage children at will without caring if children also have the right to their own lives. The implementation of this service is carried out by the lecture method. Through a psychoeducation program on toxic parenting for adolescents, it shows that participants understand and add insight regarding definitions, factors that cause toxic parenting, impacts, and strategies for dealing with toxic parenting with a more positive attitude, and strategies for managing the impact of the relationship between parents and the participants themselves. The results of this service show that the youth participants gained knowledge of the definition of toxic parenting, the factors that influence the formation of toxic parenting, the impact of toxic parenting on adolescents, and strategies for dealing with toxic parenting. Based on the results of the service, it is recommended to provide psychoeducation for adolescents so that adolescents can be better able to deal with toxic parenting with more positive strategies.